Rescue of lip switch flap at risk of necrosis due to venous congestion for cleft lip deformity. Issue 1 (1st January 2016) - Sugiyama, Madoka; Saijo, Hideto; Kazuto, Hoshi; Takato, Tsuyoshi
Abstract: In a 21-year-old male with bilateral cleft lip who developed marked venous congestion of a lip switch flap, we returned the grafted flap to the donor site to improve blood circulation of the flap and then re-transplanted it, which prevented flap necrosis. Here, we report the procedure and case.